Informação Non-GAAP: evidências do seu value relevance, e uma análise do trade-off entre oportunismo e eficiência na qualidade do seu reporte - Silva, Geisa Cassiana Paulino da (2018)
Non-GAAP are performance measures based upon adjusted accounting data adjusted or non-accounting data. The general objective of this paper was to verify the Non-GAAP information relevance, with and without explicit regulatory determinations, and later investigate a possible trade-off between the opportunistic and efficiency incentives in relation to the quality of non-GAAP reporting in the Brazilian capital market. The two Non-GAAP measurements studied were EBITDA and adjusted EBITDA, which are more disclosed Non-GAAP measures made by company managements (KPMG .2016). In Chapter 2, we analyzed non-financial stocks listed on the Brasil Bolsa Balcão (B3), active between the years of 2010 to 2016. The results show that CVM EBITDA, as the NonGAAP measure most frequently reported by companies, is also the most persistent in terms of incremental association and relative to stock returns, when these are calculated more precisely at the time of disclosure of the companies' financial statements. This CVM EBITDA result is persistent both using quantile regression and linear regression, although adjusted EBITDA and standardized EBITDA have not performed as well. Therefore, considering the verified value relevance of CVM EBITDA, although for the adjusted EBITDA the same result is not verified, hypothesis I of this study was not partially rejected. In Chapter 3, using the Logit model with panel data (2011-2016) taking into account that the dependent variable had been measured by a score that ranged between 1 and 4 in the quality of the report of the Non-GAAP measure. The results show a distinct behavior, where the quality of EBITDA CVM suffers direct positive influence from the CVM Statute 527/12 , although the quality of the adjusted EBITDA report does not present the same influence. The likelihood of EBITDA CVM be reported with higher quality increases when large companies disclose the use of this measure and after CVM regulation, but that likelihood decreases when analyst coverage increases, and when the net profit per share of the company beats analysts consensus. As for adjusted EBITDA, the relationship found between growth companies and the greater likelihood of reporting an quality adjusted EBITDA agrees with the third hypothesis of this paper. It is justified by the greater presence of non-recurring items in growth companies, thus the Non-GAAP report would seek to lower the effects of these non-recurring items on management released operating results. In relation to leverage, to infer that companies in debt are more likely to report an adjusted EBITDA of higher quality due to scrutiny from lenders, assumes, among other things, the use of this measure in debt contractual clauses, which is a matter beyond the scope of this paper. Therefore, the main contributions of this paper are: discuss alternative measures of financial performance within the context of NonGAAP information; show empirical evidence of the relevance of this type of information in the Brazilian market, as well as highlight the existence of opportunistic motivations (EBITDA CVM) and informative motivations (adjusted EBITDA) for quality NonGAAP information reports.